Farmers’ Livelihood Capital and Its Impact on Sustainable Livelihood Strategies: Evidence from the Poverty-Stricken Areas of Southwest China - Yueyue He (Sustainability, 2022)
Evaluating the influence of livelihood capital on livelihood strategies remains an unexplored strategy intended to cultivate the level of livelihood capital, enhance livelihood strategies, combine the achievements regarding a reduction in poverty, and attain everlasting poverty mitigation, along with endorsing sustainable livelihoods. Based on the survey data of 508 farmers within poverty-stricken areas of Southwest China, the entropy method was primarily used for measuring the level of farmers’ livelihood capital. Moreover, the logistic regression model was used to empirically analyze the impact of livelihood capital on the choice and transformation of livelihood strategies. The results showed the following: (1) The five categories of livelihood capital values were generally not high. The value of physical capital was the highest (0.4279), while the value of financial capital was the lowest (0.2018). (2) Physical capital, alongside natural capital, has a positive influence on the pure agriculture livelihood strategy, while human, social, and financial capital have a positive impact on the non-agriculture livelihood strategy. Excluding financial capital, the remaining types of capital have a positive impact on the part-time agriculture livelihood strategy. (3) Decisive factors are used to promote transformation from pure agriculture to part-time agriculture, mostly comprising social network support and family labor force, among other indicators. The important factors used to promote transformation from pure agriculture to non-agriculture are mainly labor education level and social network support, among other indicators. Finally, on the basis of the above findings, policy sanctions are proposed from the observations of livelihood capital and livelihood strategies.